Youth Basketball Athlete’s Anxiety When Competing Based on Gender - Herdinan, Naufal Juwan; Fitri, Mustika; Williyanto, Septian (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2023)
The study's goal is to find out how athlete worry affects teenage basketball players based on their gender. Quantitative random selection is used in this study method. A lift is used for the tools in this work. Angket is a way to receive data that is done through g from distribution. Angket used the CSAI-2R, which stands for the Competitive State Anxiety Inventory. A tool called CSAI-2R can be used to find out how anxious an athlete is during a race. The statistics software SPSS version 26 was used to look at the data for this study. According to the study's results, there were no significant changes in anxiety levels between male and female athletes. This meant that neither male nor female athletes were more likely to have the anxiety levels that teenage basketball players do.